PENGARUH NET PROFIT MARGIN, DEBT TO EQUITY RATIO DAN EARNING PER SHARE TERHADAP RETURN SAHAM - Moh Yudi Mahadianto; Siti Nur Hadiyati; Astri Harfiandita (IAIN Syekh Nurjati Cirebon, 2020)
AbstractThe study aims to examine the effect of Net Profit Margin, Debt to Equity Ratio and Earning Per Share on stock returns in consumer goods industry sector companies listed in Indonesia Stock Exchange (IDX) period 2014-2018. The type of research used is basic research using quantitative methods. The population in this study consumer goods industry sector companies amounted to 51 companies listed in Indonesia Stock Exchange (IDX). The sampling selection used purposive sampling technique, the sample are 115 samples. Statistical methods this study used to descriptive statistical analysis, the classic assumption in the from of normality test, multicolinearity test, heteroscedaticity test and autocorrelation test, multiple regression analysis, coefficient of determination test (R2) and hypothesis testing conducted with t (partial). The result of this study indicate that EPS has an effect on stock returns, while NPM and DER do not effect stock returns on the consumption sector companies listed in Indonesia Stock Exchange (IDX) period 2014-2018